Optimizing Job Satisfaction Through Providing Incentives, Providing Work Facilities, and Leadership Style in CV MSMEs. Bima TKBM Services - Suprianto, Suprianto; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the factors that influence employee job satisfaction at CV MSMEs. Bima, with a focus on incentives, work facilities and leadership style. The background to this problem arises from the importance of job satisfaction in increasing employee productivity and retention. The method used was in-depth interviews with five employees from various backgrounds, including loading and unloading workers and supervision. The research results show that all informants agree that financial incentives really motivate them and contribute to family welfare. Work facilities such as BPJS health and work safety equipment are also considered important for comfort and safety. In addition, a democratic and open leadership style creates a positive work atmosphere, increasing motivation and satisfaction. Based on these findings, it is recommended that CV management. Bima continues to improve incentive policies, ensure adequate work facilities, and maintain a supportive leadership style. These steps are expected to increase employee job satisfaction, which will ultimately have a positive effect on overall company productivity and performance.